Invasive shrub (Lantana camara L.) alters the tree diversity and ecosystem-level carbon pools in tropical forests of Central India - Lone, Parvaiz Ahmad; Kothandaraman, Subashree; Dar, Javid Ahmad; Hakeem, Khalid Rehman; Khan, Mohammed Latif (Frontiers in Forests and Global Change, 2025)
Tropical forests, known for their biodiversity and carbon (C) richness, face significant threats from biological invasions that disrupt structural and functional processes. Lantana camara (Family: Verbenaceae) is an invasive shrub that has spread across several Indian landscapes. The present study aimed to assess the changes in tree species richness and total ecosystem carbon (TEC) storage in Lantana camara-invaded (LI) and uninvaded (UI) sites in the tropical dry deciduous forests of Madhya Pradesh, India. Significantly lower species richness (SR), C storage of juveniles, total trees, and total biomass C were observed in LI sites than in UI sites. However, significantly higher C storage of shrubs + herbs (understorey), litter, and soil organic carbon (SOC) were found in LI sites than in UI sites. The percent allocation of C in tree juveniles, adults, understorey, detritus, and SOC to the TEC pool was 2.6, 39.1, 1.4, 5.5, and 51.3 in LI sites and 3.8, 49.7, 0.2, 4.0 and 42.3 in UI sites, respectively. The C stocks of tree juveniles, adults, and herbs were lower by 23.3, 15.7 and 20.3%, respectively, in LI sites than in UI sites, whereas shrub, detritus, and SOC stocks were higher by 95.1, 9.1 and 7.9%, respectively, in LI sites than in UI sites. A significant negative relationship was observed between L. camara density and SR, tree juvenile C, herb C, understorey C, and total ecosystem C storage, while the same had a significant positive relationship with shrub C, litter C, and SOC. The present findings revealed that the plant diversity and total C pools were altered by shrub invasion and have important implications for their quantification in these tropical forests.